Hidden intrahospital mortality for cerebro vascular diseases in the Intermediate Care Unit service. A five year period from 2000 to 2004. - Rubén Bembibre Taboada; Diosdania Alfonso Falcón; Julio Cortizo Hernández; Niurka Galende Hernández; Carlos Jaime Geroy Gómez; Julio Jova Hernández (Medisur)
Introduction: mortality is one of the trustable and necessary indicator for the analysis of the sanitary situation of a community, and a data source that satisfies an ample cover that allows to define strategies in health actions upon a given population. Objective: to describe aspects related with hidden mortality by cerebrovascular diseases in Intermediate Care Unit. Method: Descriptive and retrospective study of a series of cases carried out during the period 2002-2004 in the hospital ¨Dr. Gustavo Aldereguía Lima¨ of Cienfuegos. All monthly reports of the cerebrovascular diseases attention group were analysed, these being gathered from digitalized data bases from the Hospital Statistics Department (n=3477). An enquiry was applied to obtain information as: year and month of hospitalisation; egress state; decease place if in case; stay; and type of cerebrovascular disease. The deceased necropsy protocols were analysed. Results: The hidden mortality was of 0.05; the main causal entity was the cerebral infarction (71,87%), the behaviour was similar in the five years, the average stay of deceased patients in Intermediate Care Unity was of 4.2 days, and outside this Unity: 8.7 days. It was proved the reduced inn hospital hidden mortality caused by cerebrovascular diseases with lethality definition by these entities during the first days in progressive care. A reduced percent of patients died in other units where an average stay doubles that of the Intermediate Care Unit, and as the main cause: the polymorbility associated to bronchopneumonia.